Update On Hearing Loss - Bahmad, Fayez Jr (IntechOpen, 2015)
Update on Hearing Loss encompasses both the theoretical background on the different forms of hearing loss and a detailed knowledge on state-of-the-art treatment for hearing loss, written for clinicians by specialists and researchers. Realizing the complexity of hearing loss has highlighted the importance of interdisciplinary research. Therefore, all the authors contributing to this book were chosen from many different specialties of medicine, including surgery, psychology, and neuroscience, and came from diverse areas of expertise, such as neurology, otolaryngology, psychiatry, and clinical and experimental audiology.